Micropillar compression deformation of single crystals of Co3(Al,W) with the L12 structure - Chen, Zhenghao M.T.; Okamoto, Norihiko L.; Demura, Masahiko; Inui, Haruyuki (Scripta materialia, 2016)
The compression deformation behavior of single-crystal micropillars of L12–Co3(Al,W) has been investigated at room temperature as a function of pillar size and crystal orientation. The critical resolved shear stress (CRSS) obeys an inverse power-law scaling against pillar size and is independent of orientation. With the bulk CRSS value of Co3(Al,W) at room temperature estimated by extrapolating the size dependence of CRSS for micropillars, comparison of high-temperature strength is made on the CRSS values for Co3(Al,W) and Ni3Al-based compounds. Co3(Al,W) has turned out not to be strong enough to provide excellent high-temperature strength for Co-based superalloys, at least for ternary composition. [Display omitted]